‘File Xxviii/10 Report on Present Conditions in Muscat and Dealings of the State with the Tribes Nominally Under It.’ - East India Company (1924)
The file contains correspondence in the form of reports and diaries circulated between British Officials. The reports are concerned mainly with internal affairs in Muscat and Oman. The British Political Agent and Consul at Muscat reports to the Political Resident in the Persian Gulf, Bushire, on the present conditions in Muscat and the situation of failure between the state and the tribes nominally under it. The Political Agent also provides half-yearly statements of the revenue of the Muscat State finance along with comments on Bertram Sidney Thomas’ financial reports. Among other issues included in the reports are: the news of collecting (alms) money from various regions in Oman and Muscat and people’s reaction to that zakat the news of collecting (alms) money from various regions in Oman and Muscat and people’s reaction to that Shaikh ‘Isa bin Salih’s diplomacy in bringing conflicting tribes together the clashes between the two main Omani factions, the Hanawi and the Ghafiri the Wahhabis’ occupation of al-Buraimi in the1800s, and how they influenced some of the tribes of al-Dhahira region who still identify themselves as Wahhabis the relation between the Sultan of Muscat and Shaikh 'Isa bin Salih al-Harthi and his father Shaikh Salih bin Ali before him the issue of succession of Sultan Taimur bin Faisal the need of the British to protect al-Buraimi from the Wahhabis a summary of the history of Oman, its sect, the establishment of the (religious leadership) and the ruling family founded in 1744 Ibadhi a summary of the history of Oman, its sect, the establishment of the (religious leadership) and the ruling family founded in 1744 Imama a summary of the history of Oman, its sect, the establishment of the (religious leadership) and the ruling family founded in 1744 the rebellions of 1895 and 1913 The last report in the file is of the visit of the Senior Naval Officer to the Trucial Coast in May 1931, and his notes on the internal affairs in Ras al-Khaimah and Dubai.
Genre: Archival file

Enquête sur l'habitation rurale des indigènes de la Tunisie : faite par ordre Lucien Saint, résident général de France à Tunis - Bernard, Augustin (J. Barlier, 1924)
p. 33-38 plan de maison rurale de Djerba (Adjim, Guellala, Arkou, Beni Maaguel, Cedouikech, Midoun, Mahboubine) p. 95-96 : statistique d'habitations à Djerba
Keywords: Architecture – Djerba

Adventures in Tripoli: a doctor in the desert - Griffin, Ernest H. (1924)
Pp. 96 ff.: the author in Yefren, and on Sul. al-Barūnī, with photographs. The manuscript of this book was completed just before the outbreak of World War I.
Keywords: Bārūnī; Sulaymān al- (1870-1940); Récits de voyage – Djebel Nefousa

al-Dhahab al-Khāliṣ al-Munawwah bi’l-ʿIlm al-Qāliṣ - Iṭfayyish, Muḥammad b. Yūsuf (al-Maṭb. al-Salafiyya, 1924)

ملخص تاريخ الخوارج - سليم, محمد شريف (مطبعة التقدم, 1924)
Keywords: Kharijisme

هذا شرح أبي داود سليمان الجربي على متن ايساغوجي في علم المنطق لامام الصناعة ودستور البراعة أثير الدين مفضل بن عمر الأبهري - الأبهري, المفضل بن عمر أثير الدين; الجربي, أبي داود سليمان (المطبعة التونسية, 1924)
Keywords: Philosophie islamique – Logique

Le prince Jaffar - Duhamel, Georges (Mercure de France, 1924)
Keywords: Littérature – Djerba

Notes d'ethnographie et de linguistique nord-africaines - Biarnay, Samuel (Ernest Leroux, 1924)
Les dattiers dans l'oasis de Berriane p. 164-265
Keywords: Linguistique – Mzab